Univesality of Islamic Fintech: Surely or Fantasy? - Imama Zuchroh (Jurnal Ilmiah Ekonomi Islam, 2021)
This study moves on from the question of whether the Islamic financial system will be able to detect the conventional economic system? Of course, with various data on transaction volume that continues to increase over time from financial industry products that have been labeled sharia such as Sharia stocks, Islamic bonds or sukuk, and Islamic mutual funds the question will easily find the answer. And when the latest industrial revolution also changed the map of the financial industry with the development of technology and information to give birth to financial technology that is so phenomenal. So can sharia fintech a marriage between technology and islamic moral concepts become an instrument of global financing in the future? With qualitative methodology and descriptive approaches to various references to financial technology as a source of data, and the growth of Islamic fintech in non-Muslim countries that are increasingly boisterous in developing Sharia fintech, then the richness of Sharia fintech in this world, surely or just a fantasy?